2022
DOI: 10.5194/gmd-15-745-2022
|View full text |Cite
|
Sign up to set email alerts
|

Reconsideration of wind stress, wind waves, and turbulence in simulating wind-driven currents of shallow lakes in the Wave and Current Coupled Model (WCCM) version 1.0

Abstract: Abstract. Wind stress, wind waves, and turbulence are essential variables and play a critical role in regulating a series of physical and biogeochemical processes in large shallow lakes. However, the parameterization of these variables and simulation of their interactions in large shallow lakes have not been strictly evaluated owing to a lack of field observations of lake hydrodynamic processes. To address this problem, two process-based field observations were conducted to record the development of summer and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Theoretical studies have indicated that the response of a depth-variable lake to a strong uniform wind often leads to the formation of two counter-rotating gyres, also known as a double-gyre or dipole (Csanady, 1973;Bennett, 1974;Shilo et al, 2007), as was confirmed by early numerical simulations (Simons, 1980). With increased computational power, threedimensional (3D) hydrodynamic models with higher accuracy, stability and resolution have since been developed and have significantly contributed to the understanding of lake circulation, especially that driven by wind (e.g., Beletsky et al, 1999;Laval et al, 2005;Beletsky and Schwab, 2008;Bai et al, 2013;Mao and Xia, 2020;Lin et al 2022;Wu et al 2022). Recent numerical simulations have also highlighted the role of baroclinicity induced by gradients of surface buoyancy (mainly surface heating and cooling), which can enhance the large-scale circulation in the Great Lakes (Schwab and Beletsky, 2003;Bennington et al, 2010;Verburg et al, 2011;McKinney et al, 2012).…”
mentioning
confidence: 99%
“…Theoretical studies have indicated that the response of a depth-variable lake to a strong uniform wind often leads to the formation of two counter-rotating gyres, also known as a double-gyre or dipole (Csanady, 1973;Bennett, 1974;Shilo et al, 2007), as was confirmed by early numerical simulations (Simons, 1980). With increased computational power, threedimensional (3D) hydrodynamic models with higher accuracy, stability and resolution have since been developed and have significantly contributed to the understanding of lake circulation, especially that driven by wind (e.g., Beletsky et al, 1999;Laval et al, 2005;Beletsky and Schwab, 2008;Bai et al, 2013;Mao and Xia, 2020;Lin et al 2022;Wu et al 2022). Recent numerical simulations have also highlighted the role of baroclinicity induced by gradients of surface buoyancy (mainly surface heating and cooling), which can enhance the large-scale circulation in the Great Lakes (Schwab and Beletsky, 2003;Bennington et al, 2010;Verburg et al, 2011;McKinney et al, 2012).…”
mentioning
confidence: 99%
“…The correlation coefficient between the wind speed and turbidity was the largest (r = 0.57, p < 0.05). Global studies have shown [33][34][35] that wind is the main driving force of sediment resuspension in shallow lakes. Therefore, we developed the LSTM-based turbidity model using synchronous wind speed.…”
Section: Turbidity Wind and Chl-a During In Situ Observationsmentioning
confidence: 99%
“…The water-air interface is an important component in tracking and modeling changes in the water and energy cycles through wind-driven surface water dynamics [1,2]. Wind induces waves and seiches and increases evaporation rates over lakes, for example [3,4].…”
Section: Introductionmentioning
confidence: 99%